أحكام جرائم الإهمال المادي في قضايا الأسرة دراسة مقارنة بين الفقه الإسلامي والقانون الجزائري - صغراوي, عائشة; مخنان, باهية; صغراوي, سارة (University of Eloued-جامعة الوادي, 2022)
"هذه الدراسة الموسومة ب ""أحكام جرائم الإهمال المادي في الفقه الإسلامي والقانون الجزائري""، والتي كان إشكالها الرئيسي "" ما مدى توافق المشرع الجزائري مع الفقه الإسلامي في جرائم الإهمال المادي؟""، والذي عملنا للإجابة عنه برسم خطة ثنائية المباحث، خصصنا الأول لبيان الإطار المفاهيمي لجريمة الإهمال المادي بين الفقه الإسلامي والقانون الجزائري، فيما اهتم المبحث الثاني بجريمة الامتناع عن تسديد النفقة بين الفقه الإسلامي والقانون الجزائري. وقد توصل البحث إلى عدد من النتائج أهمها: اهتمام الفقه الإسلامي بأحكام النفقة وحماية حقوق المرأة المسلمة ذلك أن الشريعة ثابتة ومستقرة وتتماشى مع كل قوانين التشريع الجزائري وتطورات أحداث المجتمع في كل زمان، وذلك بوضع منظومة أخلاقية، وتكوين مؤسسات خاصة تعمل على التوجيه وعلاج المشاكل الزوجية. ""This study is tagged with ""Provisions of crimes of material neglect in Islamic jurisprudence and Algerian law"", whose main problem was ""How compatible is the Algerian legislator with Islamic jurisprudence in crimes of material negligence?"", Which we worked to answer by drawing a two-investigative plan, we devoted the first to clarifying the conceptual framework The crime of material neglect between Islamic jurisprudence and Algerian law, while the second topic concerned the crime of refraining from paying alimony between Islamic jurisprudence and Algerian law. The research reached a number of results, the most important of which are: the interest of Islamic jurisprudence with the provisions of alimony and the protection of the rights of Muslim women, because Sharia is fixed and stable and in line with all laws of Algerian legislation and developments in society at all times, by setting up a moral system, and forming special institutions that work on guidance and treatment of marital problems . "
مذكرة ماستر
Keywords: الجرائم-الاهمال المادي- النفقة; crimes, material neglect, alimony.